ANALISIS KINERJA KEUANGAN: SESUDAH DAN SEBELUM KRISIS EKONOMI GLOBAL 2008 PADA PERUSAHAAN MANUFAKTUR DI INDONESIA - Miswanto Miswanto; Vajrin Syawaluddin Aslan (BALANCE: Jurnal Akuntansi, Auditing dan Keuangan, 2019)
This study aims to analyze the financial performance of Indonesian manufacturing companies after and before the global economic crisis of 2008. In this study, financial performance is measured by Return on Assets (ROA), Return on Equity (ROE) and Net Profit Margin (NPM). By comparing the average ROA, ROE and NPM before after and before the crisis, the results of testing with descriptive analysis can be stated that ROA, ROE and NPM after the crisis are higher than before the crisis. Thus financial performance after crisis has increased compared to before the crisis. Based on descriptive analysis, it can be found that the performance of financial manufacturing companies after the the crisis is better than before crisis. Based on the t test, the results of testing on ROA, ROE and NPM are as follows. First, the ROA after the crisis showed greater than before the 2008 global economic crisis and the increase was said to be significant. Second, the ROE after the crisis showed greater than before the global economic crisis, but was not statistically significant. Third, the NPM after the crisis also showed greater than before the crisis, but it was not statistically significant.Thus, the finding with the t test shows that financial performance as measured by ROA, its performance after the crisis increases compared to before the crisis.